Effects of exposure to estradiol and estradiol plus testosterone on the mongolian gerbil (Meriones unguiculatus) female prostate - Da Silva, Diego Augusto Lopes; Zanatelli, Marianna; Shinohara, Filipe Zardini; Góes, Rejane Maira [UNESP]; Dos Santos, Fernanda Cristina Alcântara; Vilamaior, Patricia Simone Leite [UNESP]; Taboga, Sebastião Roberto [UNESP] (Wiley, 2013)
The female prostate is a differentiated organ found in several mammal species, including humans and rodents. This gland has been related to important functions on female reproductive biology. Although the factors, which regulate prostate's development and activity are not well known, its functionality has been related to steroid hormones. It is well established that cyclic changes of estradiol and progesterone levels promote histophysiological adaptations of the whole female body. In contrast, only a few is found about those adaptations in female prostate. Thus, this study aimed to evaluate the effect of estradiol and estradiol+testosterone association on gerbil female prostate in order to verify, which hormonal associations are necessary to its homeostasis. For this, adult females had the ovaries surgically removed. After recovering, they received estradiol and estradiol+testosterone doses through 30 days, each 48 h. The prostatic tissue underwent morphological and morphometric-estereological analysis. Hormonal restriction caused great gland involution and decreased secretory activity, aspects that were reverted by exposure to estradiol and estradiol+testosterone. However, these hormones were not able to re-establish the normal prostate histoarchitecture. The immunoreaction of steroid receptors (ER-α, ER-β, and AR) responded differently among the experimental and control groups, and PCNA assay showed a decrease in epithelial cell proliferation within groups that had hormone privation. Therefore, we conclude that estradiol and testosterone are able to influence prostate morphophysiology and the maintenance of gland homeostasis depends on a balance among these and other hormones. © 2013 Wiley Periodicals, Inc.
Keywords: Immunohistochemistry; Morphology; Ovariectomy; Secretion; androgen; estradiol; estrogen; testosterone; animal; cytochemistry; cytology; drug effect; female; gerbil; histology; human; immunohistochemistry; male; prostate; Androgens; Animals; Estradiol; Estrogens; Female; Gerbillinae; Histocytochemistry; Humans; Male; Prostate; Testosterone; Mammalia; Meriones unguiculatus; Rodentia